Pengaruh Aplikasi Trichoderma sp. Pada Campuran Media Tanam Pasir Sungai dan Kompos Terhadap Produksi Tanaman Sawi Hijau (Brassica chinensis var. parachinensis) - Octaviani, Nurul Walidah; Putra, Ramadhani Eka (Universitas Batanghari, 2024)
Soil degradation now is a common phenomenon found in agriculture. Thus, it is necessary to develop an alternative soilless growth media. Sand, an abundance material and relatively neglected has the potency to be develop into alternative soilless growth media. However, this material needs to be enhanced prior the application as growth medium. One of the possible methods to accomplish this is by application of compost to improve the organic material of sand and the decomposition process of this material may improve the quality of sand as growth medium. In this study, Trichoderma sp. was applied as decomposer of compost which incorporated to sand. The effect of this procedure was observed on the subject of its nutrient content, bulk density, dan porosity along with the effect on growth and productivity of Pakcoy (Brassica chinensis var. parachinensis). The result showed application of both compost and Trichoderma sp. improve C-organic, N-organic, and porosity while there were no effect on P-total, K-total, and bulk density. Pakcoy growth on the application growth medium showed improvement on growth, number of leaves, chlorophyll content of leaves, root length and weight, and harvested weight than sand although still lower than soil. Based on this study, application compost and Trichoderma sp. on sand could improve its quality as alternative growth medium.